2017
DOI: 10.12911/22998993/76701
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Napropamide Dissipation and its Effect on Soil Enzymatic Activity

Abstract: This paper assesses the dissipation of napropamide and its impact on the activity of dehydrogenases, alkaline phosphatase, acid phosphatase, and urease in sandy clay loam. The experiment was carried out on soil samples with organic carbon content of 12.08 g·kg -1 , total nitrogen content of 0.97 g·kg -1 , and pH 5.24 with the following variable factors: (a) dose of Devrinol 450 SC formation (containing 450 g of napropamide in dm 3 ): 0 (control), 0.5, 1, 2, 4, 8, and 16-fold hold of field dose; (b) day of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…According to many authors (Bielińska et al 2013 ; Bartkowiak et al 2017 ; Błońska et al 2017 ; Onyszko et al 2017 ; Lemanowicz et al 2018 ), the enzymatic tests facilitate the evaluation of both the effect of natural factors and the human impact on ecosystem functioning. The highest activity of acid phosphatase resulted from the fact that phosphomonoesterases are enzymes most susceptible to changes in soil reaction (Dick et al 2000 ), the optimum pH of soil for the activity of alkaline phosphatase was 9.0–11.0, and for acid phosphatase, 4.0–6.5.…”
Section: Discussionmentioning
confidence: 99%
“…According to many authors (Bielińska et al 2013 ; Bartkowiak et al 2017 ; Błońska et al 2017 ; Onyszko et al 2017 ; Lemanowicz et al 2018 ), the enzymatic tests facilitate the evaluation of both the effect of natural factors and the human impact on ecosystem functioning. The highest activity of acid phosphatase resulted from the fact that phosphomonoesterases are enzymes most susceptible to changes in soil reaction (Dick et al 2000 ), the optimum pH of soil for the activity of alkaline phosphatase was 9.0–11.0, and for acid phosphatase, 4.0–6.5.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of enzyme activity could be the effect of destroying microorganisms living in soil by an excessive amount of fungicides (Ye et al 2018). Inhibition of soil enzyme activity was also proved by Onyszko et al (2017). They reported that the application of excessive doses of napropamide demonstrated high toxicity towards dehydrogenases, acid phosphatase, alkaline phosphatase and urease.…”
Section: Resultsmentioning
confidence: 99%